INVESTING IN INFORMATION TECHNOLOGY AND ITS IMPACT ON FINANCIAL PERFORMANCE - Lafta, Salam Tariq; Al-Azma, Shadi (PT. Antis International Publisher, 2024)
Objective: This study investigates the impact of investment in information technology (IT) on the financial performance of private sector banks in Mosul, addressing the strategic importance of IT in organizational development. Method: Employing a descriptive-analytical approach, data were collected through an electronic questionnaire distributed to employees in three private banks, covering the period from August 1 to October 18, 2024. The study relied on statistical analysis, including correlation and regression techniques, to test the hypothesized relationships between IT investment and financial performance. Results: The findings reveal a statistically significant impact of IT investment on financial performance, with a computed F-value of 8.648 exceeding the tabular value of 4.089 at a significance level of 0.05. The correlation coefficient (0.431) indicates a strong positive relationship between IT adoption and financial outcomes, emphasizing IT’s critical role in enhancing bank performance. Novelty: This research contributes to the ongoing discourse on IT and productivity by providing empirical evidence from a developing economy, specifically in the banking sector. It underscores the necessity of creating robust IT infrastructure and optimizing IT resources to improve financial performance, offering valuable insights for both practitioners and policymakers in leveraging technology for competitive advantage in dynamic financial environments.